Composite Developable Alternative Surfaces (MATEMATIKA, 2012)
Developable alternative patches is introduced as a choice in the design of developable surfaces. This paper extends the previous work by joining consecutive alternative patches subject to various continuity conditions. With a first boundary curve freely specified, $2n + 3, n + 4$ and 5 DOF's are available for a second boundary curve of a developable alternative surface containing $n$ patches, when the surface is $G^0, G^1$ and $C^1$ continuity, respectively. The composite surfaces are then evaluated by using highlight lines, which effectively in detecting surface irregularities. Keywords: Developable surfaces; degrees of freedom; highlight lines 2010 Mathematics Subject Classification: 65D10, 65D17